Developmental physical education for all children theory into practice - Donnelly, Frances Cleland 1951-; Mueller, Suzanne S. 1947-; Gallahue, David L. (Human Kinetics, 2017)
Developmental Physical Education for All Children, Fifth Edition, features the following benefits : Shows teachers how to translate child development theory and research from the psychomotor, cognitive, affective, and fitness domains into practice ; Offers teachers the understanding they need to create developmentally appropriate lessons that align with the new SHAPE America National Standards for Physical Education with grade-level outcomes, assessments, and instructions on implementing learning goals for students in pre-K through grade 5 ; Provides multiple standards-based movement experiences for pre-K through grade 5 learners that include movement tasks and extensions, scaled learning environments, skill cues, practice strategies, teaching style choices, and formative assessments aligned with goals ; Supplies learning goal blueprints that integrate specialized skills, movement concepts, and tactics for developmental games, dance, and gymnastics. The result of this comprehensive overhaul of a standard classic is that both future and current teachers will be prepared and equipped to provide high-quality developmental physical education that can help children be physically active now and throughout heir lives. -- Back cover